Dapur Maja Sdn. Bhd. / Imanina Nadia Jamalludin ... [et al.] - Imanina Nadia, Jamalludin; Farah Liyana, Rosli; Siti Nur Ainani, Amran; Ahmad Khalis, Johan; Nurul Athirah, Alang Bahwandi (2019)
Dapur Maja Sdn. Bhd. offers product and services of sambal called SomeHeat to retailers who will be selling it directly to consumer, providing a multipurpose product that suits everyone’s taste. Our target market is the male and female working adults and students who wants to cook a proper dish fast with minimal time. We also targeted that all level of income class people is suitable for our product as it offers affordable price. SomeHeat is multipurpose, from eating with nasi lemak to cook it with shrimp and it can be consumed by all ages. As our business is currently in Ipoh, our product will be delivered to retailers who will sell it to the customers across Malaysia. As people are getting busier, the demand for ready-to-eat food is higher and this can boost our growth as we provided the supply to satisfy consumers’ demand. Ready-to-eat Sambal have been introduced to the market by our competitors such as Sambal Che Nor and Sambal Che Peah. These businesses have been established before us, but we are introducing the new version of sambal, SomeHeat which is moist and gravy-like texture differs from our competitors. Customers can also modify the sambal to their liking. Our source of revenue is mostly from our retailers who will be selling our product. SomeHeat will be in a box of 12 jars amounting to RM144 and the freight will be charged based on the location delivered. The management of Dapur Maja Sdn Bhd consists of 5 lead manager which is Imanina Nadia as the general manager, Farah Liyana as the marketing manager, Siti Nur Ainani as the administrative manager, Ahmad Khalis as the operational manager and Nurul Athirah as the financial manager. We are responsible as partners in this business.